Findings from cardiovascular evaluation of NCAA Division I collegiate student-athletes after asymptomatic or mildly symptomatic SARS-CoV-2 infection - Hwang, C. E.; Kussman, A.; Christle, J. W.; Froelicher, V.; Wheeler, M. T.; Moneghetti, K. J. (Clinical Journal of Sport Medicine, 2021)
Objectives: The risk of myocardial damage after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has been controversial. There is an urgent need for data to support the appropriate level of cardiovascular screening for safe return-to play. The purpose of this study is to report the incidence of abnormal cardiovascular findings in National Collegiate Athletic Association (NCAA) Division I student-athletes with a history of SARS-CoV-2 infection. Methods: This is a case series of student-athletes at a single NCAA Division I institution who tested positive for SARS-CoV-2 by polymerase chain reaction (PCR) or antibody testing (IgG) from 4/15/2020 to 10/31/2020. From 452 athletes who were screened, 5,124 PCR and 452 antibody tests were completed. Student-athletes were followed through 12/31/2020 (median 104 days, range 64-182 days). Cardiac work-up included clinical evaluation, troponin level, electrocardiogram (ECG), and echocardiogram. Additional work-up was ordered as clinically indicated. Results: 55 student-athletes tested positive for SARS-CoV-2. Of these, 38 (69%) had symptoms of Coronavirus Disease (COVID-19), 14 (26%) had a positive IgG test, and 41 (74%) had a positive PCR test. Eight abnormal cardiovascular screening evaluations necessitated further testing including cardiac magnetic resonance imaging (cMRI). Two athletes received new cardiac diagnoses, one probable early cardiomyopathy and one pericarditis, while the remaining six had normal cardiac MRIs. Conclusion: These data support recent publications which recommend the de-escalation of cardiovascular testing for athletes who have recovered from asymptomatic or mildly symptomatic SARS-CoV-2 infection. Continued follow-up of these athletes for sequelae of SARS-CoV-2 is critical.